CHNS analysis towards food waste in composting - Abdul Rahman, Muhammad Firdaus; Abu Samah, Mohd Armi; Abd Halim, Khairul Bariyyah (Zibeline International Publishing, 2018)
High food waste generation in Malaysia that reached up to 15, 000 tonnes per day assign for major problems towards environment, economy and social aspect. Alternative method had been studied for the past years, but composting was seen among the best possible solution to treat this matter. Composting not only has an environmentally method but it also produces a valuable end product that will benefit in agricultural sector. Further studies had been done in this paper to represent their macro and micro nutrient quality as well as their bioavailability towards plant and the analysis of data collected in both CHNS analyser and mathematical method using ultimate analysis. This study also applied enhanced composting process with its segregation, drying, grinding and standard aeration time. Each container has been rotated for 5 minutes yet different resting time was applied which are 25, 55, 155 minutes namely A, B, C and D within 2 hours period. Result shown that overall Carbon (C), Nitrogen (N) and Sulphur (S) concentration increases as the higher aeration was applied while the Hydrogen vice versa. The highest elemental percentage distribution recorded is carbon (31%) while the lowest recorded is S (0.115%). The data collected from Ultimate Analysis was seen not applicable to be use as it has the same content as food waste after composting. The compound molecular formula recorded was C29H7N5S. Regarding ratio of carbon to nitrogen results, it was found that it ranged from 5.39 to 5.71% for different compost treatment under study, where the lowest value of C and N ratio (5.39%) for sample C and the highest value (5.71%) was obtained for sample B with all has the same C/N ratio which is 6: 1 which suitable range in application of soil amendment. Therefore, this study found a significant relationship between chemical factors and compost formation which contribute to better analysis, especially to food waste management.